A novel layout of air-cooled condensers to improve thermo-flow performances. (1st March 2016) - Chen, Lei; Yang, Lijun; Du, Xiaoze; Yang, Yongping
Highlights: A novel vertical arrangement of air-cooled condensers is proposed. Novel air-cooled condenser flow rate markedly increases compared with the current. Inlet air temperature of novel air-cooled condensers equals to ambient temperature. Novel ACCs utilize wind power to improve the thermo-flow performances. Novel ACCs can be applied to the direct dry cooling system design in power plants. Abstract: Ambient winds are generally unfavorable to the thermo-flow performances of air-cooled condensers in power plants. More emphases are placed to weaken the negative effects of ambient winds, but no layout alternative of air-cooled condensers is considered. In this work, a novel vertical arrangement of air-cooled condensers is proposed on the basis of a 2 × 600 MW direct dry cooling power plant, which can weaken the adverse wind effects and utilize the wind power to improve the cooling capacity of air-cooled condensers. By means of the CFD simulation and experimental validation, the flow and temperature fields of cooling air for the vertically arranged air-cooled condensers at ambient winds are obtained. The mass flow rate, inlet air temperature and turbine back pressure are computed and compared with the traditional air-cooled condensers. The results show that the flow rate of the novel air-cooled condensers increases conspicuously compared with the current ones both in the absence and presence of winds. In the wind directions of 60° and 90°, the off-axis flow distortions of axial flow fans are greatly weakened and the average inlet air temperature of the novel air-cooled condensers is reduced and almost equals the ambient temperature. The thermo-flow performances of the air-cooled condensers are improved, thus the turbine back pressure is reduced by the novel layout of air-cooled condensers.